Relationship Between Blood Cytokine Levels, Psychological Comorbidity, and Widespreadness of Pain in Chronic Pelvic Pain - Karshikoff, Bianka; Martucci, Katherine T.; Mackey, Sean (Frontiers in Psychiatry, 2021)
Background: Low-grade inflammation has been implicated in the etiology of depression, long-term fatigue and chronic pain. TNFα and IL-6 are perhaps the most studied pro-inflammatory cytokines in this the field of psychoneuroimmunology. The purpose of our study was to further investigate these relationships in patients with chronic pelvic pain specifically. Using plasma samples from a large, well-described sample of patients with pelvic pain and healthy controls via the Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network, we examined the relationship between TNFα and IL-6 and comorbid psychological problems. We also investigated the relationship between IL-8 and GMCSF, and how widespread the pain was. Methods: We included baseline blood samples in the analyses, 261 patients (148 women) and 110 healthy controls (74 women). Fourteen pro- and anti-inflammatory or regulatory cytokines were analyzed in a Luminex® xMAP® high-sensitivity assay. We used regression models that accounted for known factors associated with the outcome variables to determine the relationship between cytokine levels and clinical measures. Results: There were no statistical differences in cytokine levels between patients and healthy controls when controlling for age. In patients, TNFα was significantly associated with levels of fatigue (p=0.026), but not with pain intensity or depression. IL-6 was not significantly related to any of the outcome variables. Women with pelvic pain showed a negative relationship between IL-8 and widespreadness of pain, while men did not (p=0.003). For both sexes, GM-CSF was positively related to how widespread the pain was (p=0.039). Conclusion: Our results do not suggest low-grade systemic inflammation in chronic pelvic pain. Higher TNFα blood levels were related to higher fatigue ratings, while higher systemic GM-CSF levels predicted more widespread pain. Our study further suggests a potentially protective role of IL-8 with regard to how the pain spreads in the body, at least for women.